2021
DOI: 10.3390/cancers13040765
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Correlates of γδ T Cell Infiltration in Triple-Negative Breast Cancer

Abstract: The prognostic impact of the different tumor-infiltrating lymphocyte (TIL) subpopulations in solid cancers is still debated. Here, we investigated the clinicopathological correlates and prognostic impact of TILs, particularly of γδ T cells, in 162 patients with triple-negative breast cancer (TNBC). A high γδ T cell density (>6.625 γδ T cells/mm2) was associated with younger age (p = 0.008), higher tumor histological grade (p = 0.002), adjuvant chemotherapy (p = 0.010), BRCA1 promoter methylation (p = 0.010)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
(111 reference statements)
1
13
0
Order By: Relevance
“…In order to study the role of CXCR2 and its possible link with immune infiltration in TNBC patients, we analyzed the densities of CD11b (a marker of granulocytes), CD66b (a marker of neutrophils) and CXCR2-positive cells on a cohort of 290 samples from patients with TNBCs that we had previously characterized for both their phenotypic characteristics and their immune microenvironment [ 37 , 38 ]. The main characteristics of the studied population are described in Table 1 and are consistent with the classical characteristics of TNBCs (for further details, refer to Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to study the role of CXCR2 and its possible link with immune infiltration in TNBC patients, we analyzed the densities of CD11b (a marker of granulocytes), CD66b (a marker of neutrophils) and CXCR2-positive cells on a cohort of 290 samples from patients with TNBCs that we had previously characterized for both their phenotypic characteristics and their immune microenvironment [ 37 , 38 ]. The main characteristics of the studied population are described in Table 1 and are consistent with the classical characteristics of TNBCs (for further details, refer to Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…CD11b, CD66b and CXCR2 expression was analyzed by immunohistochemistry of serial sections from the same TMA blocks used in our previous studies [ 7 , 36 , 37 , 38 ]. For this study, we used anti-CD11b rabbit monoclonal Ab (clone EP45 at 1/400, BioSB, Santa Barbara, CA, USA), anti-CD66b mouse monoclonal (clone 80H3 at 1/200, BioRad, Marnes-la-Coquette, France) and the recently validated anti-CXCR2 mouse monoclonal antibody (clone E-2 at 1/500, Santa Cruz Technology, Dallas, TX, USA) as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human solid cancers, γδ tumour-infiltrating lymphocytes (TILs) have been proposed by many studies to be relevant prognostic factors; however, there appear to be differences in their anti-tumour functions across different solid cancer types. Notably, their tumour infiltration and cytolytic activity have been linked with a beneficial role for patient outcome in gastric cancer [ 121 , 122 ], hepatocellular carcinoma [ 68 ], ovarian cancer [ 123 ], colorectal cancer [ 124 , 125 ], renal cell carcinoma [ 126 , 127 ], glioblastoma [ 128 ] and triple-negative breast cancer [ 129 , 130 , 131 ]. On the other hand, they were also reported to have a negative impact on prognosis in ovarian cancer [ 37 ] and oral cancer [ 42 ], and conflicting studies also found them to positively correlate with pathogenesis in colon cancer [ 132 ] and breast cancer [ 133 , 134 ].…”
Section: Anti-tumour Functions Of γδ T Cellsmentioning
confidence: 99%
“… 48 Similar to our results, a recent study found that, in triple negative breast cancer, PIK3CA mutations were not associated with the density of tumor-infiltrating lymphocytes. 49 However, other studies seem to highlight an association between PI3K/Akt activation and immune suppression in breast, prostate, and bladder cancers. 50 - 52 Further research should be performed to better understand these dynamics in glioma.…”
Section: Discussionmentioning
confidence: 99%